Implementation of Bruner’s Learning Theory to Improve Understanding of Mathematical Concepts in Lower Grade Students of SDN Cimrutu 01 Patimuan with the Aid of Concrete Objects - Ani Oktafiana; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
This classroom action research aims to improve the understanding of mathematical concepts, especially on measurement material, in class III SDN Cimrutu 01 Patimuan through the application of Bruner's learning theory with the help of concrete objects. The background of this research is the difficulty of lower grade students in understanding mathematical concepts that tend to be abstract. The main focus of the research is the use of Bruner's approach, which emphasizes three stages of representation (enactive, iconic, and symbolic), as well as the use of concrete objects as intermediaries for understanding. The research was conducted in three cycles, each of which includes the planning, action implementation, observation, and reflection stages. The research subjects consisted of 20 class III students of SDN Cimrutu 01 Patimuan, with a composition of 10 male students and 10 female students. Data on understanding of mathematical concepts were obtained through learning outcome tests at the end of each cycle and at the pre-cycle stage. The results of the study showed a significant increase in learning completeness, from 25% in the pre-cycle to 90% in Cycle III. In Cycle I, learning completion reached 65%, then increased to 85% in Cycle II, and finally reached 90% in Cycle III, with most students meeting the Learning Target Completion Criteria (KKTP) of at least 70. The consistency of this increase shows that the application of Bruner's theory assisted by concrete objects is effective in improving understanding of mathematical concepts, especially in measurement material in lower grades. The learning strategy that begins with concrete experiences, continues with visual representations, and ends with symbolic understanding is proven to be in accordance with the stage of students' cognitive development. This study concludes that mathematics learning based on Bruner's theory through the use of concrete objects can be an effective alternative to improve students' understanding of mathematical concepts, especially in abstract material.